2014
DOI: 10.1016/s1995-7645(14)60250-9
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents the structural changes induced in the rats' deep cerebellar nuclei by sodium metabisulfite, a preservative agent

Abstract: Curcumin, the main part of the turmeric, could prevent the structural changes induced in the deep cerebellar nuclei by sodium metabisulfite, a preservative agent, in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Sulfite metabolism generates an intermediate product called sulfur trioxide radical that may act in some toxic effects of sulfite, including increment of lipid peroxidation, impairment of DNA synthesis, and destruction of amino acids according to Niknahad and O'Brien (2008). These results partially agreed with Karimfar, et al (2014) who stated that the volume and number of neurons of deep cerebellar nuclei were evaluated in sodium metabisulfite-treated rats. The kidneys showed Proliferation and congestion of the glomerular tuft, the presence of hyaline cast in the lumen of the renal tubules and Periglomerular and intertubular mononuclear leukocyticbinfiltration.…”
Section: Discussionsupporting
confidence: 72%
“…Sulfite metabolism generates an intermediate product called sulfur trioxide radical that may act in some toxic effects of sulfite, including increment of lipid peroxidation, impairment of DNA synthesis, and destruction of amino acids according to Niknahad and O'Brien (2008). These results partially agreed with Karimfar, et al (2014) who stated that the volume and number of neurons of deep cerebellar nuclei were evaluated in sodium metabisulfite-treated rats. The kidneys showed Proliferation and congestion of the glomerular tuft, the presence of hyaline cast in the lumen of the renal tubules and Periglomerular and intertubular mononuclear leukocyticbinfiltration.…”
Section: Discussionsupporting
confidence: 72%
“…In the same manner, curcumin‐loaded lipid nanoparticles revealed a higher ameliorative effect than free curcumin in reversing the pathological alterations induced by aluminum chloride in mice brain section (Kakkar & Kaur, 2011 ). In addition, several studies on curcumin and curcumin‐loaded nanoparticles have reported the combined antioxidant and anti‐inflammatory roles of free curcumin and nanoencapsulated curcumin using different nanoparticles in neurodegenerative diseases (Huang et al, 2017 ; Karimfar et al, 2014 ; Li et al, 2016 ; Noorafshan et al, 2013 ; Partadiredja et al, 2013 ; Sandhir et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxic effects (decrease in volume of deep cerebellar nuclei and number of neurons) were seen after oral sodium metabisulfite administration at 25 mg/kg bw per day (corresponding to 17 mg SO 2 equivalents/kg bw per day) for 56 days in the study by Karimfar et al. (2014). It is noted that these effects were abrogated by concomitant dosing with an antioxidant, curcumin.…”
Section: Appendix B – Summary Of Toxicity Studies Considered Sufficie...mentioning
confidence: 99%
“…From the oral studies of Karimfar et al. (2014) and Noorafshan et al. (2015), the Panel noted that there were effects at 17 mg SO 2 equivalents/kg bw per day on neurons, glia and synaptic plasticity.…”
Section: Assessmentmentioning
confidence: 99%